Quaestiones super quattuor libros Sententiarum. - Marsilius, of Inghen, -1396; Hoenen, Maarten J. F. M., 1957-; Erne, Markus (Philosopher) (Studies in the history of Christian traditions ;, 2015)
Marsilius of Inghen's Commentary on the Sentences evinces the history of Scholasticism between Ockham and Luther. The part edited here discusses the Trinity revealing new evidence on the debates among Realists and Nominalists at the Universities of Paris and Heidelberg.